Factors associated with serious infections in patients hospitalized with systemic lupus erythematosus - Noriega-Zapata, Erika Janeth (2022)
Introduction. Lupus patients have an increased risk of developing infections due to the disease, use of immunosuppressants and corticosteroids. Objective. To identify the associated factors for serious infections in lupus patients in a national referral hospital. Retrospective, analytical, case-control study in the Rheumatology Service of the Guillermo Almenara Irigoyen National Hospital, Lima, Peru. Methods. The registry of hospitalized patients in the study period was analyzed, the cases were patients in whom the etiology of the first infection developed their hospitalization. Controls were hospitalized lupus patients without infections in the same study period. Variables predisposing to the development of infections were analyzed. Results. 61 patients out of 390 hospitalized developed infections during their hospitalization. 48 developed 1 only infectious event (in 40 an etiology developed). The cases had higher damage, activity and comorbidity compared to the controls. In the univariate analysis, salary (p = 0.031), use of immunosuppressants upon admission (previous: p = 0.004 and current: p = 0.004), use of glucocorticoids (<30 days: p = 0.015 and> 30-360 days: p = 0.028), activity (p = 0.029) and damage (p = 0.026) produced by the disease and length of hospitalization (p = 0.045), had a statistically significant association. In the multivariate analysis, the days of hospitalization were associated with the development of infections. Conclusions. There is an association between days of hospitalization and the development of serious infections in lupus patients in the study period.